Epilepsy, electroacupuncture and the nucleus of the solitary tract - (:unkn) unknown (British Medical Acupuncture Society, 2006)
Vagal nerve stimulation and electroacupuncture have some promise as neuroprotective therapies for patients with poorly controlled epilepsy. It has been demonstrated that stimulation of acupuncture points on the extremities results in stimulation of the vagus nerve. It is possible that the antiepileptic effects of these two applications might be targeting the same centre in the brain. The nucleus of the solitary tract, which is a primary site at which vagal afferents terminate, is also the site for afferent pathways of facial, scalp and auricular acupuncture via trigeminal, cervical spinal and glossopharyngeal nerves. Taken together with laboratory findings, the neuroprotective pathways of electroacupuncture in epileptic models may stem from the collaboration of its anti-inflammatory and neurotrophic actions through the nucleus of the solitary tract via vagus nerve stimulation.
Keywords: Acupuncture; Epilepsy; Nucleus solitary tract